Fast biodiesel production using K2Fe3O4 catalyst for CH3O• radical-mediated transesterification of soybean, Jatropha and Ricinus oils - Adriana N. Gutiérrez-López; Ricardo I. Rodríguez-Ramírez; Violeta Y. Mena-Cervantes; Fabiola S. Sosa-Rodríguez; Ulises M. García Pérez; Luis Lartundo Rojas; Jorge Vazquez-Arenas; Raúl Hernández-Altamirano (Energy Conversion and Management: X)
The catalysis of potassium ferrate (K2FeO4) is herein tested towards the heterogeneous transesterification with three triglyceride sources: Jatropha curcas L. oil (JCO), Ricinus communis oil (RCO), and industrial soybean oil (SBO). A Box-Behnken experimental design (BBD) is used to maximize the biodiesel production screening the following factors: stirring speed (125 to 700 RPM), methanol to oil molar ratio (6:1–16:1), catalyst load (0.15 to 6 wt%). The optimized reaction conditions resulting from a response surface methodology (RSM) allowed maximum conversions of 97.26, 95.85, and 74.85 % for JCO, SBO and RCO in 1 h, respectively. While these optimal performances were found adopting the following collected factors: stirring speed: 293, 357 and 433 RPM; Catalyst dosage: 3.28, 4.40, and 4.11 wt%; Methanol to oil molar ratio: 16:1, 16:1, and 11:1 for JCO, SBO and RCO, respectively. Transesterification reactions are monitored at different times revealing that 5 min is enough to reach conversions higher than 95 % for JCO and SBO, owing to the CH3O• formation rapidly attacking the double bonds of triglyceride, diglyceride and monoglyceride. Proton nuclear magnetic resonance (1H NMR) is used to prove the methyl esters production, Fourier Transform Infrared Spectroscopy (FTIR), and Gas Chromatography to identify the fatty acid profiles of each oil; while acid number, density, viscosity, and oxidative stability are determined for the three oils and their corresponding methyl esters. Additionally, heating value, flash point, cloud point, and pour point are measured for the biodiesel produced according to the ASTM D6751.